Novel dielectric material of solid-state energy storage battery brick as well as preparation method and application of novel dielectric material

A dielectric material formula for solid-state energy storage batteries addresses high production costs and safety concerns by using a combination of sea sand, diatomaceous earth, and other components, enhancing performance and enabling applications in infrastructure.

CN119230157APending Publication Date: 2024-12-31YANTAI MAIXIN NEW ENERGY TECHNOLOGY DEVELOPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411454793.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Current automotive batteries face high failure rates, high production costs, environmental toxicity, and safety concerns, particularly in lithium and nickel-cadmium batteries, limiting their widespread adoption in new energy vehicles.

Method used

A new dielectric material formula for solid-state energy storage batteries, composed of fine sea sand, diatomaceous earth, alum, sodium carbonate, manganese oxide, and graphite, is used to create a solid-state battery brick with improved electrochemical performance and safety, featuring a simple preparation process.

Benefits of technology

The new dielectric material reduces production costs, enhances safety, and improves energy storage performance, making it suitable for infrastructure applications such as electric heating tiles and offering environmental benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a novel dielectric material of a solid-state energy storage battery brick and a preparation method and application thereof, and is characterized in that the novel dielectric material comprises pure fine sea sand, diatomite, alum, sodium carbonate, high-purity manganese oxide, graphite conductive powder, sodium carbonate and pure seawater, which are uniformly mixed in proportion and repeatedly stirred and extruded to form a flocculent solid state; applying a sheet with the thickness of 2 mm on the positive plate; and extruding the residual solid dielectric material around the battery, and continuously extruding and shaping to form a square solid to obtain the energy storage battery brick. The light weight, large energy and low production cost can be realized, and the raw materials are extracted from mineral resources, are non-toxic and harmless, and can be energy-saving, environment-friendly and pollution-free. The recycled battery material can also be used for manufacturing an environment-friendly electric heating plate, so that environment-friendly pollution-free circulation is realized, and the risk of combustion explosion of the battery in the use process is greatly reduced. The method can be applied to the field of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a new dielectric material of a solid-state energy storage battery brick, a preparation method and application thereof, and belongs to the technical field of batteries. Background Art

[0002] At present, the demand for new energy vehicles is rising continuously. However, power batteries, as the "heart" of new energy vehicles, are in short supply and facing a "battery shortage". At present, a large number of car ordering users have encountered the embarrassing phenomenon of dealers raising prices in disguise and not being able to pick up the car for a long time. As a result, major new energy vehicle companies have also encountered a return crisis. Although many new energy vehicle companies have chosen to purchase, participate in shares, and independently develop to strive to achieve breakthroughs in the production and supply of power batteries, they have never been able to achieve their goals due to various constraints such as technical barriers, shortage of raw materials, high costs, and long production cycles.

[0003] The three most popular automotive batteries on the market currently have production problems and usage defects as follows: 1. Lithium batteries: The failure rate is high, with about 1% of the batteries failing for various reasons; they cannot tolerate overcharging or over-discharging, and excessive charging and discharging will shorten their service life; the raw materials are expensive, the production cost is high, and the material stacking density is low, which is not conducive to production control; multiple protection mechanisms are required, and improper use will not only reduce the service life but may also cause an explosion.

[0004] 2. Nickel-cadmium batteries: The cadmium in nickel-cadmium batteries is toxic, so nickel-cadmium batteries are not conducive to the protection of the ecological environment. In addition, due to numerous shortcomings, nickel-cadmium batteries have been basically eliminated from the application range of vehicle batteries.

[0005] 3. NiMH battery: There are thermal problems, large charging current, low charging efficiency, and a lot of heat; low battery specific energy; low nominal voltage, higher requirements for battery consistency and reliability; poor high temperature charging performance, thermal runaway may occur, resulting in safety problems; large self-discharge; high material cost. NiMH batteries use a lot of relatively expensive metals such as nickel and cobalt, which makes the cost of battery raw materials relatively high.

[0006] In view of this, it is indeed necessary to provide a new dielectric material formula for monomer-combined solid-state energy storage batteries with low production cost, excellent electrochemical performance and excellent safety performance. Summary of the invention

[0007] One of the purposes of the present invention is to provide a new dielectric material for solid-state energy storage battery bricks, which has a low production cost, excellent electrochemical performance and excellent safety performance. The new dielectric material formula of the monomer combination solid-state energy storage battery is used to reduce the battery production cost and improve the battery safety performance. It can achieve environmental protection of materials and green environmental protection recycling and reuse.

[0008] Another object of the present invention is to provide a method for preparing a new dielectric material for solid-state energy storage battery bricks. The process preparation process is simple, the dielectric material is environmentally friendly and in a solid state, and the environmentally friendly battery dielectric molding can greatly improve the environmental performance and energy storage performance of the battery.

[0009] Another purpose of the present invention is to be used in the field of solid-state energy storage batteries and can be expanded to infrastructure; due to its excellent energy storage characteristics, it can be used as electric heating wall tiles, electric heating floor tiles, etc. for paving the ground and building walls, and converting daytime solar energy into battery bricks for storage to continue to generate electricity. In this way, whether it is a factory or a building for heating and power generation, a large amount of electricity resources will be saved. At the same time, it has the advantages of not taking up space, being environmentally friendly, safe, non-flammable, non-explosive, and non-combustible, which will bring us huge economic benefits and environmental value. Using it in infrastructure will bring new directions in the industrial structure.

[0010] In order to achieve the above-mentioned purpose, the technical solution of the present invention is implemented as follows: a new dielectric material for solid-state energy storage battery bricks, characterized in that the formula includes: 25-26.5g of fine sea sand, 12-12.5g of diatomaceous earth, 7-8g of alum, 7-8g of sodium carbonate, 8-9g of high-purity manganese oxide, 6-6.5g of graphite conductive powder, 6.5-7g of sodium carbonate water, and 11.1 ml of pure seawater.

[0011] The fine sea sand is 25.5g of fine sea sand soaked in seawater with a mesh size of 250-300 or more.

[0012] The diatomaceous earth has a fineness of more than 300 meshes and weighs 12.2 g.

[0013] The alum is 7.5g of medicinal or edible alum.

[0014] The graphite conductive powder is ultrafine 6.3g.

[0015] The sodium carbonate solution is 6.8 g of granular edible alkali.

[0016] The sodium carbonate is 7.7g.

[0017] The high-purity manganese oxide is 8.6 g.

[0018] A method for preparing a new dielectric material for a solid-state energy storage battery brick comprises the following steps: Step 1, prepare a mixture of new solid energy storage dielectric materials: prepare in a sterile vacuum chamber, first mix the above materials evenly according to the proportion, first put in powdered materials fine sea sand 25-26.5g, diatomaceous earth 12-12.5g, alum 7-8g, sodium carbonate 7-8g, high-purity manganese oxide 8-9g, graphite conductive powder 6-6.5g, sodium carbonate water 6.5-7g, then put in liquid material pure seawater 11.1 ml, mix all and stir evenly to form a flocculent solid dielectric material for use; Step 2: Take out 10 grams of the solid dielectric material obtained in step 1, squeeze it into a 2 mm sheet and apply it on the positive electrode plate; wherein the solid dielectric material is kept in a constant temperature and humidity environment within the range of 20°C-25°C and the humidity is controlled between 30%-40%; Step three, take out the remaining solid dielectric material in step one, squeeze it around the battery, and continue to squeeze it to form a square solid to obtain an energy storage battery brick.

[0019] The positive effect of the present invention is that it can be made into an energy storage battery through simple assembly. The battery formula medium forms a voltage of 1.56 volts before charging. After 5 times of rapid charging and discharging, the voltage can reach 2.8-3.5V as measured by a multimeter. The output current is much larger than the current of a 1.5V battery, which can reach 2-3 times. The results of multiple experiments show that the current does not change much during multiple charging, but the current gradually increases during the discharge process, and the experimental light bulb becomes brighter and brighter, indicating its superior performance in energy storage. Its performance, size, weight and environmental protection are all better than other batteries. This data is measured under the condition of extremely simple packaging. Subsequent improvement of production technology and perfecting of sealing conditions can further improve the battery performance.

[0020] The solid-state energy storage battery brick of the present invention can be expanded in the field of infrastructure in terms of its application: due to its excellent energy storage characteristics, it can be used as electric heating wall bricks, electric heating floor bricks, etc. for paving and building walls, and converting daytime solar energy into battery bricks for storage and continued power generation, so that whether it is a factory or building heating power generation, it will save a lot of power resources, and at the same time, the advantages of not taking up space, environmental protection, safety, no fire, no explosion, and non-flammable will bring us huge economic benefits and environmental protection value. Use in infrastructure will bring new directions in the industrial structure. DETAILED DESCRIPTION

[0021] The present invention and its beneficial effects are further described in detail below in conjunction with specific embodiments, and the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0022] A method for preparing a new dielectric material for a solid-state energy storage battery brick comprises the following steps: Step 1, prepare a mixture of new solid energy storage dielectric materials: prepare in a sterile vacuum chamber, first mix the above materials evenly according to the proportion, first put in powdered materials fine sea sand 25g, diatomaceous earth with a fineness of more than 300 meshes 12g, medicinal alum 7g, sodium carbonate 7g, high-purity manganese oxide 8g, 2000 mesh ultrafine graphite conductive powder 6g, sodium carbonate water 6.5g, and then put in liquid material pure seawater 11.1 ml, mix all and stir evenly to form a flocculent solid dielectric material for use; Step 2: Take out 10 grams of the solid dielectric material obtained in step 1, squeeze it into a 2 mm sheet and apply it on the positive electrode plate; wherein the solid dielectric material is kept in a constant temperature and humidity environment within the range of 20°C-25°C and the humidity is controlled between 30%-40%; Step three, take out the remaining solid dielectric material in step one, squeeze it around the battery, and continue to squeeze it to form a square solid to obtain an energy storage battery brick.

[0023] Example 2 A method for preparing a new dielectric material for a solid-state energy storage battery brick comprises the following steps: Step 1: Prepare a new solid energy storage medium material mixture: Prepare in a sterile vacuum chamber, first mix the above materials evenly according to the proportion, first put in powdered materials fine sea sand 26.5g, diatomaceous earth with a fineness of more than 300 meshes 12.5g, edible alum 8g, sodium carbonate 8g, high-purity manganese oxide 9g, 2000 mesh ultrafine graphite conductive powder 6.5g, sodium carbonate water 7g, and then put in liquid material pure seawater 11.1 ml, mix all and stir evenly to form a flocculent solid medium material for standby use Step 2: Take out 10 grams of the solid dielectric material obtained in step 1, squeeze it into a 2 mm sheet and apply it on the positive electrode plate; wherein the solid dielectric material is kept in a constant temperature and humidity environment within the range of 20°C-25°C and the humidity is controlled between 30%-40%; Step three, take out the remaining solid dielectric material in step one, squeeze it around the battery, and continue to squeeze it to form a square solid to obtain an energy storage battery brick.

[0024] Example 3 The material formula provided in this embodiment is as follows: 25.5g of fine sea sand, 12.5g of diatomaceous earth with a fineness of more than 300 meshes, 7.5g of medicinal alum, 7.7g of sodium carbonate, 8.6g of high-purity manganese oxide, 6.3g of 2000 mesh ultrafine graphite conductive powder, 6.8g of sodium carbonate water, and 11.1 ml of pure seawater as liquid material. Step 1: Prepare a mixture of new solid-state energy storage medium materials: The experimental environment is best configured in a sterile vacuum chamber. First, mix the formula materials evenly according to the proportion, put the powdered material first and then the liquid material, and stir them all together. Since the materials are safe and environmentally friendly, they can be mixed with confidence to form a flocculent solid state, ready for use in solid-state battery bricks.

[0025] Step 2: Take out 10 grams of the dielectric material obtained in step 1, squeeze it into a sheet of about 2 mm and apply it on the positive electrode plate. The solid dielectric material is preferably kept in a constant temperature and humidity environment within the range of 20°C-25°C and the humidity is controlled between 30%-40%; Step three, take a moderate amount of the remaining dielectric material in step one, squeeze it around the battery, and continue to squeeze it to form a square solid to obtain an energy storage battery brick.

[0026] The materials of this embodiment are purchased from: simple and easy to obtain, environmentally friendly solid-state energy storage battery bricks greatly reduce the production cost, and at the same time, due to its solid-state characteristics, it greatly improves the safety of the battery, making it less likely to burn and explode due to collisions and other factors. Since the raw materials are non-toxic and harmless, energy saving, environmental protection and pollution-free can be achieved. The recycled battery materials can also be used to make environmentally friendly electric heating plates, achieving environmentally friendly and pollution-free circulation. It can be used in the field of infrastructure, and the floor tiles can be used for paving the ground or building walls.

[0027] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A new dielectric material for solid-state energy storage battery bricks, characterized in that The formula includes: 25-26.5g of fine sea sand, 12-12.5g of diatomaceous earth, 7-8g of alum, 7-8g of sodium carbonate, 8-9g of high-purity manganese oxide, 6-6.5g of graphite conductive powder, 6.5-7g of sodium carbonate water, and 11.1 ml of pure sea water.

2. A new dielectric material for solid-state energy storage battery bricks according to claim 1, characterized in that The fine sea sand with a mesh size of 250-300 or more is 25.5 g soaked in sea water.

3. The novel dielectric material for solid-state energy storage battery brick according to claim 1 is characterized in that The diatomaceous earth has a fineness of more than 300 meshes and weighs 12.2 g.

4. The novel dielectric material for solid-state energy storage battery brick according to claim 1 is characterized in that The alum is 7.5g of medicinal or edible alum.

5. The novel dielectric material for solid-state energy storage battery brick according to claim 1, characterized in that The 2000-mesh graphite conductive powder is 6.3 g.

6. The novel dielectric material for solid-state energy storage battery brick according to claim 1, characterized in that The sodium carbonate solution is 6.8 g of granular edible alkali.

7. The novel dielectric material for solid-state energy storage battery brick according to claim 1, characterized in that The sodium carbonate is 7.7g.

8. The novel dielectric material for solid-state energy storage battery brick according to claim 1, characterized in that The high-purity manganese oxide is 8.6 g.

9. The novel dielectric material for solid-state energy storage battery brick according to claim 1, characterized in that The preparation method of the novel dielectric material comprises the following steps: Step 1, prepare a mixture of new solid energy storage dielectric materials: prepare in a sterile vacuum chamber, first mix the above materials evenly according to the proportion, first put in powdered materials fine sea sand 25-26.5g, diatomaceous earth 12-12.5g, alum 7-8g, sodium carbonate 7-8g, high-purity manganese oxide 8-9g, graphite conductive powder 6-6.5g, sodium carbonate water 6.5-7g, then put in liquid material pure seawater 11.1 ml, mix all and stir evenly to form a flocculent solid dielectric material for use; Step 2: Take out 10 grams of the solid dielectric material obtained in step 1, squeeze it into a 2 mm sheet and apply it on the positive electrode plate; wherein the solid dielectric material is kept in a constant temperature and humidity environment within the range of 20°C-25°C and the humidity is controlled between 30%-40%; Step three, take out the remaining solid dielectric material in step one, squeeze it around the battery, and continue to squeeze it to form a square solid to obtain an energy storage battery brick.

10. Application of a new dielectric material for solid-state energy storage battery bricks in infrastructure materials, including floor and wall tiles.